Transition to e-learning in a Malaysian dental school during Covid-19 pandemic: Faculty experiences and future recommendations / Sahar Fatima - Sahar , Fatima (2021)
During COVID-19 pandemic e-learning has emerged as the primary mode of continuing teaching and learning activities in health professions education including dental education. Due to its high reliance on clinical and skill-based teaching the dental education has encountered challenges in maintaining quality and academic integrity ensuring competent future clinicians. The present study aims to analyze the challenges and opportunities experienced by the faculty in adversity of rapid and unprepared transition to e-learning from conventional pedagogy in order to address future strategies for efficient e-learning. A qualitative phenomenological research approach is adapted for the study. Semi-structured interviews were conducted with purposefully selected dental faculty members of a private dental school in Malaysia, using online platform and were recorded audio and video. The data was transcribed verbatim and interpretative thematic analysis was done manually. The findings revealed distinct challenges and opportunities that need to be addressed and explored further for better preparedness for possible blended learning in future as recommended by the participants. The decision to integrate elearning as a norm in health professions education, including dental education highly relies on sincere efforts from educators, institutional management, and local government authorities. A well-devised dynamic plan and policy considering resources and infrastructure, curricular structure, faculty training and development, management and standardization at institutional and national level is the need of time. The recommendations made in the present study will facilitate educators in health professions education, as well as policy makers to devise future strategies for efficient e-learning as part of blended learning or exclusive online learning in any unprecedented situation.